The referee's age and experience versus the accuracy of handball referee decisions at various levels of competition - Slowinski, B. (5th EHF Scientific Conference "Handball for Life", 21.-22.11.2019, Cologne, 2020)
The aim of the study is to examine the level of rightness referee's decisions in handball and also to determinate relations between the quality of decisions making and age as well as work experience. The main method used to assess the quality and quantity referee's decisions is categorized observation of 72 handball matches based on the research tool such as a decisions registration sheet. The referee's assessment was based on 10193 decisions and the study involved 72 referees. The results indicated that referee's made more mistakes at lower standard of competition. It was found that there is a relation between age & experience and the number of wrong and correct decisions as well as total lack of response to the violation of the rules of the game.